2016
DOI: 10.1080/21505594.2016.1159367
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the C-terminal truncations of NS1 in avian influenza A viruses and effect on virulence and replication of a highly pathogenic H7N1 virus in chickens

Abstract: (2016) Prevalence of the C-terminal truncations of NS1 in avian influenza A viruses and effect on virulence and replication of a highly pathogenic H7N1 virus in chickens, Virulence, 7:5, 546-557, DOI: 10.1080/21505594.2016 protein sequences of all AIV subtypes in birds from 1902 to 2015 were analyzed to study the prevalence and distribution of CTE truncation (DCTE). Thirteen different DCTE forms were observed in NS1 proteins from 11 HA and 8 NA subtypes with high prevalences in H9, H7, H6 and H10 and N9, N2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Apart from a polybasic cleavage site in the HA protein, other molecular markers potentially influencing the virulence were identified. C‐Terminal truncation of NS1 has been observed previously in various subtypes of AI viruses, mainly those from gallinaceous poultry (Abdelwhab et al., ). Experimental studies revealed that the effect of NS1 truncation on virus replication depends on the host and virus strain (Abdelwhab et al., ; Zielecki et al., ).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Apart from a polybasic cleavage site in the HA protein, other molecular markers potentially influencing the virulence were identified. C‐Terminal truncation of NS1 has been observed previously in various subtypes of AI viruses, mainly those from gallinaceous poultry (Abdelwhab et al., ). Experimental studies revealed that the effect of NS1 truncation on virus replication depends on the host and virus strain (Abdelwhab et al., ; Zielecki et al., ).…”
Section: Discussionmentioning
confidence: 66%
“…C‐Terminal truncation of NS1 has been observed previously in various subtypes of AI viruses, mainly those from gallinaceous poultry (Abdelwhab et al., ). Experimental studies revealed that the effect of NS1 truncation on virus replication depends on the host and virus strain (Abdelwhab et al., ; Zielecki et al., ). Similarly, truncation of the PB1‐F2 protein has been found to occur in particular hosts (mainly in mammals) (Dundon, ).…”
Section: Discussionmentioning
confidence: 66%
“…Immunohistochemical examination of consecutive sections was performed with the avidin–biotin–peroxidase complex method (Vector Laboratories) using a primary polyclonal rabbit anti-NP antibody (1:750) and a secondary biotinylated goat anti-rabbit IgG1 (Vector Laboratories) antibody (1:200) as described47. The concentration of nucleoprotein antigen was semi quantitatively assessed by scoring on a 0 to 4 severity scale for tissues: 0 = negative; 1 = single cells, 2 = scattered foci, 3 = numerous foci, 4 = coalescing foci or diffuse and on a scale of 0 to 3 for endothelium: 0 = negative; 1 = single blood vessel, 2 = multiple blood vessels, 3 = diffuse as done before48.…”
Section: Methodsmentioning
confidence: 99%
“…1 Another approach consists in analyzing the thousands of sequences that were deposited at the Influenza Virus Resource (http://www.ncbi.nlm.nih.gov/genomes/FLU/FLU.html). In a recently published article in Virulence, Abdelwhab et al 2 carried out a systematic study of C-terminal truncations of the Non-structural protein NS1 in avian influenza A viruses (IAVs) since the beginning of the 20th century. Influenza A viruses are enveloped viruses of the Orthomyxoviridae family, whose genome consists of 8 negative-strand RNAs which collectively encode more than 10 viral proteins.…”
mentioning
confidence: 99%